Promoting Citizenship and Preventing Statelessness in South Africa: A Practitioner's Guide - Lawyers for Human Rights (Pretoria University Law Press (PULP), 2014)
Promoting Citizenship and Preventing Statelessness in South Africa: A Practitioner's Guide Edited by Lawyers for Human Rights 2014 ISSN: 978-1-920538-30-9 Pages: 152 Print version: Available Electronic version: Free PDF available